Analisis Perbandingan Kinerja Keuangan Sebelum dan Sesudah Penerapan PSAK 69 pada Perusahaan Agroindustri di Indonesia - Muhlis Romadoni (Universitas Jember, 2020)
This study aims to determine and analyze the difference in financial performance proxied by current ratio, return on asset, and debt-to-asset ratio between pre and post-adoption of PSAK 69 of agroindustry companies in Indonesia. The research method used quantative method. Samples were choosen using purposive sampling method. Paired sample t-test as parametric test and wilcoxon signed rank test as non-parametric test are used to test and examine ther result of this research. The result of this research showed that (1) there is no difference in current ratio between pre and post-adoption of PSAK 69, (2) there is difference in return on asset between pre and post-adoption of PSAK 69, and (3) there is no difference in debt-to-asset ratio between pre and post-adoption of PSAK 69. Keywords: PSAK 69, Biological Assets, Financial Performance